2022
DOI: 10.2147/jir.s344321
|View full text |Cite
|
Sign up to set email alerts
|

Oral-Intestinal Microbiota in Colorectal Cancer: Inflammation and Immunosuppression

Abstract: It is widely recognized that microbial disorders are involved in the pathogenesis of many malignant tumors. The oral and intestinal tract are two of the overriding microbial habitats in the human body. Although they are anatomically and physiologically continuous, belonging to the openings at both ends of the digestive tract, the oral and intestinal microbiome do not cross talk with each other due to a variety of reasons, including intestinal microbial colonization resistance and chemical barriers in the upper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 108 publications
(123 reference statements)
0
13
0
Order By: Relevance
“…This imbalanced gut microbiota may have been attributed to gastrointestinal diseases and cancer. The association between oral microbiota and tumor development is documented by several reports [ 48 , 49 ]. For instance, the genomic analysis of colorectal adenocarcinoma tissue revealed the F. nucleatum and other Fusobacterium species enrichment [ 50 ].…”
Section: Association Between Microbiome and Cancer Developmentmentioning
confidence: 99%
“…This imbalanced gut microbiota may have been attributed to gastrointestinal diseases and cancer. The association between oral microbiota and tumor development is documented by several reports [ 48 , 49 ]. For instance, the genomic analysis of colorectal adenocarcinoma tissue revealed the F. nucleatum and other Fusobacterium species enrichment [ 50 ].…”
Section: Association Between Microbiome and Cancer Developmentmentioning
confidence: 99%
“…Because the NF-κB cascade is a central link in the communication within host-microbial interactions during the occurrence and development of BC, it induces an inflammatory microenvironment by promoting the production of pro-inflammatory cytokines, containing TNF-α, IL-1β, IL-6, and IL-8 [ 135 , 136 ]. An epidemiologic study of bladder carcinoma patients from ten geographic areas of the United States demonstrated that urinary tract infections were strongly related to squamous cell carcinoma [ 137 ].…”
Section: Microbiome-mediated Cytokines For Tumor Microenvironment Est...mentioning
confidence: 99%
“…Overall, oral and gut microbes interact through gut-oral and fecal-oral pathways, which, in turn, can form and/or reshape the microbial ecosystems in both habitats, ultimately regulating the body’s physiological and pathological processes. The oral pathogen(s) can disturb the barrier function of the intestine and invade the gut mucosa, which causes intestinal dysbacteriosis and chronic inflammation, eventually resulting in inflammatory bowel disease (IBD) [ 107 , 108 ]. A number of studies have also found that a series of oral bacteria are closely associated with CRC, by analyzing the microbial composition of the oral cavity, colonic mucosal tissue, and fecal samples from patients with CRC [ 109 ], implying that the cross-talk between microbes may also be an important mechanism of tumorigenesis in the digestive system.…”
Section: Interactions Between Gut Microbiota and Radiotherapymentioning
confidence: 99%
“…The intestinal inflammatory and immunosuppressive microenvironment created by oral-gut microbes is a key factor in the development and progression of CRC [ 108 ]. Wang et al [ 156 ] investigated the theory that sodium butyrate (NaB), a major product of gut microbial fermentation, could modulate the gut microbiota in mice with CRC liver metastasis (CLM) and improve the host immune response.…”
Section: Radiotherapy For Cancer Based On the Gut Microbiotamentioning
confidence: 99%